2001
DOI: 10.1136/heart.86.3.e8
|View full text |Cite
|
Sign up to set email alerts
|

Papillary muscle calcification after inferoposterior myocardial infarction

Abstract: Extensive papillary muscle calcification is quite a rare finding in echocardiographic examinations. A case of a 71 year old man with isolated calcification of the papillary muscles, detected by fluoroscopy and confirmed by echocardiography, is presented. Intracardiac calcifications in patients with prior right coronary artery occlusion and mitral regurgitation should suggest the possibility of posteromedial papillary muscle calcification and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Infarct size is underrepresented by the extent of calcific deposits. 2 Isolated papillary muscle calcification after myocardial infarction can also be seen 18 (Fig. 10).…”
Section: Imaging Findingsmentioning
confidence: 94%
“…Infarct size is underrepresented by the extent of calcific deposits. 2 Isolated papillary muscle calcification after myocardial infarction can also be seen 18 (Fig. 10).…”
Section: Imaging Findingsmentioning
confidence: 94%
“…Conventional echocardiography can detect only fibrosis and calcification of papillary muscles. 22 Strain analysis of papillary muscle requires special echocardiography equipment and good echocardiographic images. Conventional nuclear medicine equipment lacks sufficient spatial resolution to visualize the papillary muscle reliably except in patients with hypertrophic cardiomyopathy.…”
Section: Papmi With and Without Rupture After Stemimentioning
confidence: 99%
“…The posterior papillary muscle was involved Ϸ3 times more frequently than the anterior papillary muscle, which was consistent with previous reports. 21,22 (27) Abbreviations as in Table 3.…”
Section: Papmi With and Without Rupture After Stemimentioning
confidence: 99%
“…This shortening of the papillary muscles results in an abnormal pulling on the chordae tendineae leading to moderate–to‐severe valve regurgitation and complete rupture of the papillary muscle in some cases . Therefore, when valve regurgitation or coronary artery occlusions are discovered, papillary muscle injury and calcification should be considered as a co‐occurrence, having some association with the concomitant pathology . It has been shown that echocardiography can be advantageous in evaluating patients who present with these conditions.…”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%